Japan and a Pacific Free Trade Area - Kojima, Kiyoshi (Tokyo : University of Tokyo Press, 1971)
This volume focuses on the genesis of the Pacific Free Trade Area idea as a new design for expanding trade and for accelerating economic development both within and between advanced pacific countries and neighbouring Asian developing countries
Includes bibliographical references.
osc 24/08/2018
Loans
Keywords: Free trade; Pacific Area; Japan